2011
DOI: 10.1080/09593330.2010.540716
|View full text |Cite
|
Sign up to set email alerts
|

The application of sewage sludge as an expanding agent in the production of lightweight expanded clay aggregate mass

Abstract: Sewage sludge can be used as an expanding agent in the production of lightweight expanded clay aggregate (LECA) mass. The addition of sewage sludge increases the total porosity and decreases the bulk density of a sinter. The addition of sewage sludge to a raw material used in the production of LECA enabled a decrease in the burning temperature for the maintained operational parameters of a lightweight aggregate. The optimum content of sewage sludge added to a raw material used in LECA production was 5% to 15% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
3
14
0
Order By: Relevance
“…The closed porosity was calculated by difference between total and open porosity, and, according to Table 4, 7.9% for the internal part and 7.2% for the external shell were the values found. Similar figures were indicated in literature (Latosinska and Zygadlo, 2011) for lightweight aggregates incorporating sewage sludge as expanding agent. It is important to note that it was not possible to analyze adequately a whole aggregate through mercury porosimetry due to logistical limitations of the sample holder, whereas helium pycnometry indicated a real density of 2.44 g/cm 3 .…”
Section: Technological Properties Of Sintered Lwasupporting
confidence: 90%
See 1 more Smart Citation
“…The closed porosity was calculated by difference between total and open porosity, and, according to Table 4, 7.9% for the internal part and 7.2% for the external shell were the values found. Similar figures were indicated in literature (Latosinska and Zygadlo, 2011) for lightweight aggregates incorporating sewage sludge as expanding agent. It is important to note that it was not possible to analyze adequately a whole aggregate through mercury porosimetry due to logistical limitations of the sample holder, whereas helium pycnometry indicated a real density of 2.44 g/cm 3 .…”
Section: Technological Properties Of Sintered Lwasupporting
confidence: 90%
“…In the literature there are several studies aiming to produce LWA using secondary materials (Ducman et al, 2002;Cheeseman and Virdi, 2005;Quina et al, 2006;Chiou et al, 2006;Huang et al, 2007;Qiao et al, 2008;Gonzalez-Corrochano et al, 2009Chen et al, 2010;Kourti and Cheeseman, 2010;Latosinska and Zygadlo, 2011;Tan et al, 2012;Hwang et al, 2012) such as combustion ashes, waste glass, sewage sludge ash, incinerator bottom ash, mining residues, heavy metal sludge, washing aggregate sludge, lignite coal fly ash, contaminated mine soil. In other cases, natural materials such as zeolitic rocks or volcanoclastites were considered as well (Gennaro et al, 2004(Gennaro et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of major elements of natural clay using XRF revealed the chemical composition indicated in Table 3. Thus, the requirement for bloating materials indicated in the literature (Riley, 1951;de' Gennaro et al, 2004;Chiou et al, 2006;Gonzalez-Corrochano et al, 2009;Latosinska and Zygadlo, 2011) is observed for clay since SiO 2 : 48-70%, Al 2 O 3 : 8-25% and fluxing oxides (Fe 2 O 3 + CaO + MgO + Na 2 O + K 2 O) 4.5-31%. Indeed, Fig.…”
Section: Characterization Of Natural Claymentioning
confidence: 95%
“…Although these residues generally have limited applications, thermal treatments can produce a material that is environmentally stable, and may be further used for producing ceramics (Quina et al, 2008a). In this scope, the production of lightweight aggregates (LWA) has been considered for many secondary materials (Wainwright and Cresswell, 2001;Ducman et al, 2002;Cheeseman and Virdi, 2005;Chiou et al, 2006;Quina et al, 2006;Huang et al, 2007;Qiao et al, 2008;Gonzalez-Corrochano et al, 2009Chen et al, 2010;Kourti and Cheeseman, 2010;Latosinska and Zygadlo, 2011;Tan et al, 2012) such as combustion ashes, waste glass, sewage sludge ash, incinerator bottom ash, mining residues, heavy metal sludge, washing aggregate sludge, lignite coal fly ash, and contaminated mine soil. Indeed, LWA can be defined as materials lighter than water and more porous than sand, gravel or ground rock (commonly referred to as "dense" aggregates) and can be produced from natural resources (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…After a series of assessments of the cost and engineering characteristics, Hung claimed that the lightweight aggregate concrete met the green, environmentally friendly and recycling requirements and was suitable for areas like Taiwan with frequent earthquakes. Moreover, sewage sludge can be applied as an expanding agent in the production of lightweight expanded clay aggregate mass, and the optimum amount of sludge applied to a raw material used in such production was 5% to 15% of dry mass [7]. Yang [8] studied the addition of sewage sludge ash with other stabilized materials such as cement, fly ash and lime to improve soft subgrade soils and suggested future engineering applications.…”
Section: Introductionmentioning
confidence: 99%